(untitled) (Current Problems in Rail Vehicles, 2021)
The article is approaching and describing the implementation of static and fatigue test of the bogie frame for motor bogie frame for EMU (Electric Multiple Unit) based on ČSN EN 13749:2011. 24 hydraulic linear actuators (cylinders) were used for tests and were controlled by computer in real time together.